Mister Johnson [videorecording (DVD)] - Brosnan, Pierce; Woodward, Edward, 1930-2009; Eziashi, Maynard; Cary, Joyce, 1888-1957 (Criterion collection ;)
A Nigerian villager is eager to work as a civil servant for the British authorities, including a sympathetic district officer, in the hopes that it will benefit him in the future. Instead, his ambition leads to his tragic downfall. Mister Johnson, based on a 1939 novel by Joyce Cary, is a graceful, heartfelt drama about the limits of idealism, affectingly acted and handsomely shot.